AB0824 Evaluation of the detection of myositis-specific antibodies by lineblot as a tool for the characterisation of a prospective multicenter cohort. (12th June 2018) - Piette, Y.; Bonroy, C.; Dehoorne, J.; De Bleecker, J.; De Sloovere, M.; Van Praet, L.; Vander Mijnsbrugge, A.-S.; Jacques, P.; Vandendriessche, S.; Versaevel, M.; De Keyser, F.; Smith, V.
Abstract : Background: Traditionally, the diagnosis of idiopathic inflammatory myopathies (IIM) is based on clinical findings, muscle enzyme levels, electromyography and biopsy. Newer approaches include the detection of myositis-specific autoantibodies (MSA), with MSA identified in about 50% of patients. Today, several commercial platforms for MSA detection have become commercially available. In the context of the start-up of a prospective multicentre cohort, we evaluated the usefulness of a multiparameter line blot for the serological characterisation of patients with clinical suspicion of IIM. Objectives: To evaluate the usefulness of a multiparameter line blot for the serological characterisation of patients with clinical suspicion of IIM. Methods: A total of 225 samples (118 consecutive routine samples for which MSA were requested and 107 controls [50 systemic sclerosis (SSc), 29 systemic lupus erythematosus (SLE) and 28 rheumatoid arthritis patients (RA)]) was analysed on indirect immunofluorescence (HEp-2000, Immunoconcepts) and lineblot (MYO12 blot, D-Tek). All consecutive samples were retrospectively categorised by the treating medical specialist as definite IIM (n=16), probable IIM (n=10), immune mediated inflammatory disease (IMID) – myositis overlap not excluded (n=28), myopathic features without IIM (n=1), IIM excluded (n=44), and lost from follow-up/no data available (n=19). Data to calculate the EULAR/ACR probability score were also collected. Results: MSA were detected in 12% of the 225 samples, showing no multiple reactivities. A sensitivity of 50% in the IIM patients (definite and probable n=13/26 – based on judgement of the clinician) was observed, with the highest frequencies observed for anti-HMGCR (15%, n=4), anti-Mi2 (12%, n=3) and anti-Jo1 (12%, n=3). Less frequent antibodies were anti-EJ (n=1), anti-MDA5 (n=1) and anti-NXP2 (n=1). All these patients had a MSA-compatible clinical IIM subtype. The median minimal EULAR/ACR probability score was 97% (range 6%–100%, no biopsy data entry), with the lowest score observed in the anti-EJ patient. In contrast, MSA were also observed in 8 patients with no convincing clinical diagnosis of IIM or myositis overlap syndrome (anti-TIFγ in 4 [3 SSc and 1 SLE]; anti-SRP in 1 [1 RA]; anti-SAE in 3 [1 SSc, 1 RA and 1 IIM excluded], mostly showing low antibody titres (n=6/8) and no compatible immunofluorescence pattern on HEp-2000 (n=7/8). For 2 other positive samples the results were not conclusive (anti-PL7 in patient with myopathic features and anti-SRP in an unspecified IMID patient). Conclusions: The detection of MSA by lineblot will be useful for the prospective serological characterisation of patients with clinical suspicion of IIM. Nevertheless, careful interpretation in correlation with the clinical findings and other technical examinations is necessary in case of low titres and absence of a compatible immunofluorescence pattern. Disclosure of Interest: None declared